Rendering the paradoxes and pleasures of academic life: using images, poetry and drama to speak back to the measured university. Issue 3 (16th April 2017) - Manathunga, Catherine; Selkrig, Mark; Sadler, Kirsten; Keamy, (Ron) Kim
ABSTRACT: Measurement of academic work has become more significant than the intellectual, pedagogical, cultural, political and social practices in which academics and students engage. This shifting emphasis creates paradoxes for academics. They experience a growing sense of disconnection between their desires to develop students into engaged, disciplined and critical citizens and the activities that appear to count in the enterprise university. As measurement discourses preclude the possibilities of human emotion and hinder intellectual labour, we embarked on an arts-informed research project that established new creative spaces for our colleagues to illustrate the pleasures and paradoxes of their academic work. In the research project, we developed critical pedagogies through art and poetry that enabled academics to speak back to university management – and each other – about how they experience their work. In this paper, we draw upon poststructural 'micro-physics' of power, the poststructuralist 'politics of reinscription', and art, poetry and drama as critical pedagogies to interrogate the potential of arts-informed research to speak back to the measured university. The key contribution of this article is to recommend arts-informed methodologies as a forum for dissent and resistance at a time when the spaces of collegiality, pleasure and democracy in the measured university are under attack.